The Influence of Green Human Resource Management on Competitive Advantage: The Role of Green Innovation - Agustina Irawati; Gia Rizky (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2024)
This study aimed to analyze the influence of green human resources management on competitive advantage with green innovation as an intervening variable in the textile industry in Kabupaten Sragen. The sampling technique in this study was simple random sampling, with 115 textile industry employees as respondents. Primary data in this research were collected by questionnaire method through Google form that had been tested for validity and reliability. Data analysis in this study were descriptive statistics analysis, and classical assumption tests including normality, linearity, and heteroscedasticity tests using IBM SPSS statistic version 26. The result of the study showed that green human resource management had a positive and significant effect on competitive advantage, green human resource management had a positive and significant effect on green innovation, green innovation had a positive and significant effect on competitive advantage, and green innovation partially mediated the effect between green human resources management on competitive advantage.